2015
DOI: 10.5455/msm.2015.27.188-191
|View full text |Cite
|
Sign up to set email alerts
|

Drug Addiction as Risk for Suicide Attempts

Abstract: Introduction:Suicide is closely linked to the substances use. Therefore it is very important to confirm the factors that affect the possibility of suicidal behavior.Methodology:The survey included 200 respondents; 100 heroin addicts on the substitution program that attempted suicide and 100 opiate addicts who have not attempted suicide. The evaluation included a questionnaire with socio-demographic, hereditary and addiction data, legal problems and then the Minnesota Multiphasic Personality Inventory–MMPI-2.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 23 publications
3
40
1
7
Order By: Relevance
“…This illustrates competing risks—if dying earlier of liver‐related causes, patients do not live long enough to die of circulatory and respiratory causes,—and this should be taken into account in mortality rates and survival analysis. The higher proportion of specific sub categories of external causes—accidental poisoning with narcotics and hallucinogens—among persons with evidence of HCV compared to the general population is consistent with the studies reporting associations between suicides, accidental or drug‐related deaths and HCV …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This illustrates competing risks—if dying earlier of liver‐related causes, patients do not live long enough to die of circulatory and respiratory causes,—and this should be taken into account in mortality rates and survival analysis. The higher proportion of specific sub categories of external causes—accidental poisoning with narcotics and hallucinogens—among persons with evidence of HCV compared to the general population is consistent with the studies reporting associations between suicides, accidental or drug‐related deaths and HCV …”
Section: Discussionsupporting
confidence: 84%
“…This illustrates competing risks-if dying earlier of liver-related causes, patients do not live long enough to die of circulatory and respiratory causes,-and this should be taken into account in mortality rates and survival analysis. The higher proportion of specific sub categories of external causes-accidental poisoning with narcotics and hallucinogens-among persons with evidence of HCV compared to the general population is consis-tent with the studies reporting associations between suicides, accidental or drug-related deaths and HCV [19][20][21][22][23][24]. Interestingly, external causes were still one of the main causes ofdeath among persons with evidence of clearing HCV infection (last RNA result negative) and were significantly higher compared with those who continued to be RNA positive.…”
mentioning
confidence: 70%
“…Abubakar et al, (2014) showed that the duration of hospitalization for poisoning cases ranged from 1-41 days [39]. While mortality rate in our study was 0.8%, death rate in some other studies were 0.3% [16], 1.3% [24], 7.8% [38], 4.2 [26], and 16% [37].…”
Section: Discussioncontrasting
confidence: 53%
“…Following addiction, psychiatric disorders were common in our ndings. Dragisic et al, (2015), found that psychiatric history and addiction were the most common amongst patients committed suicide [37]. Senanayake and Karalliedde (1988) showed that intentional poisonings in cases between 11-30 years old in Serilanka happened in people with a history of psychiatric disorder [38].…”
Section: Discussionmentioning
confidence: 99%
“…should have greater supervision on drug programs of patients with mental health problems. Moreover, legal limitations should be applied on the delivery of drugs to individuals who visit drugstores and ask for drugs without a prescription [50]. In this research, 4.3% of the participants reported opium abuse.…”
Section: Discussionmentioning
confidence: 79%